Safety assessment on GMO products: a review / Umi Sarah Khadri - Khadri, Umi Sarah (Faculty of Plantation and Agrotechnology, 2018)
By 2050, it is predicted that the food production will increase about 70% in the countries with developing economies. It was estimated 40 that years later the population will increase together with the demand of the food. One way to solve the problem is by using genetically modified crops which are major product of global in food industry. As we know, the struggle against pest and disease encourages more GM crops to be produced. However, rapid growth of GM crops into agricultural practice has caused a debate due to direct or indirect effect on human and environment. Despite enhanced yield potential, risk and biosafety concerns related to GM crops are the main issues need to be addressed. A review to assess safety on GM crops is necessary to prove the safety of GM crops. The objectives of this review are to review safety and nutrition value of GMO‟s products with non-GMO‟s products and to review an evaluation of GM products relative to both human health and environment. A multicomponent safety assessment was applied on GM crops to ensure that they are safe as food from non-GM crops in term of allegenicity, toxicity, adverse nutrition change and gene flow. The GMO‟s products safety was currently observed.